Global migration and factors that support acculturation and retention of international nurses: A systematic review. (December 2022) - Pressley, Charlene; Newton, Dillon; Garside, Joanne; Simkhada, Padam; Simkhada, Bibha
Abstract: Background: International nurses (migrant nurses who are recruited to work in different countries) make essential contributions to global health and care workforces that are experiencing domestic nurse shortages. Global recruitment and migration is increasing, and with growing dependency on international nurses, health and care employers must understand their lived experiences if they want to support acculturation and subsequent retention. Aim: This paper reports a systematic review of qualitative literature on the experiences of international nurses working overseas. The aim is to explore the lived experiences of international nurses working and living in different countries globally. We argue their experiences shape socialisation and contribute to longer term retention of this fundamental nursing workforce. Method: A systematic literature search was carried out in Medline, CINAHL, PsychInfo, PubMed and Web of Science for global research publications from 2010 to 2020. Research studies conducted in Australia, Canada, New Zealand, the United Kingdom and the United States were identified, quality appraised and subjected to data extraction/analysis. Findings: The findings of twenty seven papers were synthesised into six themes: (1) individual and organisational preparedness, (2) communication and the art of language, (3) principles and practices of nursing, (4) social and cultural reality, (5) equality, diversity and inclusion, and (6) facilitators of integration and adaptation. Discussion: Whilst experiences are multifaceted and complex, factors shaping acculturation of international nurses were transferable across various countries. Individual motivations for migration should be recognised, and short term, transitional and long term needs must be identified to support development needs and ongoing career progression. Cultural integration and language barriers should be sensitively managed to enable effective acculturation. Culturally sensitive leadership is also key to ensuring zero tolerance of inappropriate racist and discriminatory behaviours. Conclusion: Health and care employers offer tangible benefits for international nurse workforces and in culturally compassionate and professional sociocultural environments, international nurses can thrive. However, to effectively retain this workforce in the longer term, significant improvement is required across a number of areas. Tweetable abstract: This new systematic review paper explores the factors that can support acculturation and retention of internationally-recruited nurses globally. Highlights: Nursing workforce shortages are an issue of international concern, with the gap between demand for services and limited supply of nurses widening. Countries impacted by nursing shortages have recruited internationally to fill vacancies, with many countries now dependent on international nurses to meet domestic shortages. Despite the success of overseas recruitment drives in attracting international nurses, there has been limited attention to the supporting acculturation and the longer term retention of an important nursing workforce. International nurses can experience challenges and frustrations alongside unique learning needs that makes their transitional period difficult. Through examining the lived experiences of international nurses, we identify factors that shape acculturation and may support retention of this key workforce. To support retention of international nurses, health care providers must increase support and development opportunities to meet their expectations and aspirations.